THE EFFECTIVENESS OF THE USE OF “MojiGoiGo!” FLASH-BASED LEARNING MEDIA TOWARDS THE RESULTS OF THE JLPT-LIKE - Adnyani, Kadek Eva Krishna; Sadyana, i Wayan; Hermawan, Gede Satya (LPPM Undiksha, 2018)
The research aimed to know the effectiveness of the use of “Mojigoigo!” flash-based learning media towards the results of the JLPT-Like of the second-semester students majoring in Japanese Language Education of Ganesha Education University. The method used in the study was the experimental research method with the Pre-Experimental Design and the form used was One Group Pretest – Posttest Design. The instruments used were pre-test and post-test in the form of multiple choice questions which the material was equivalent of JLPT (JLPT-Like). The data analysis employed the t-test analysis. On the results of t-test, it retrieved (the value of sig. =0.006<0.05), meaning that on the statistical hypothesis Ho is rejected and the Ha is accepted, stating that